Nutrient digestibility in South African abalone (Haliotis Midae L.) - Sales, James (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2002)
The evaluation of potential alternative protein sources for the formulation of least-cost optimal diets to satisfy the nutrient requirements of South African abalone (Haliotis midae) has been hampered by the absence of a suitable, practical, replicable and reliable digestibility technique. A suitable lowcost faeces collection technique was developed in this study to obtain suitable quantities of excreta for analysis from this species. Acid-insoluble ash was identified as a reliable, replicable and safe internal marker in comparison to chromic oxide and crude fibre for use in nutrient digestibility studies with H. midae. This was validated by the consistency and repeatability of the results and by comparison to total collection of faeces. The traditional substitution method used in digestibility studies with fish to evaluate protein digestibility of feed ingredients was found to be unsuitable for H. midae. Apparent protein digestibility values exceeding 100 % derived through this method could be attributed to associative effects between feed ingredients, differential diet and faecal nutrient leaching, and mathematical artifacts in calculations when using substitution versus single protein diets. An ingredient particle size of less than 450 Î¼m in comparison to particle size classes of above 450 Î¼m was shown to enhance nutrient (dry matter, organic matter, protein, fat) digestibility and minimise dry matter leaching from diets. The dietary inclusion level of both pre-gelatinised maize starch and a-cellulose did not influence (P > 0.05) apparent nutrient (protein, fat, fiber, starch) digestibility. Using the above digestibility protocol amino acid availability of all plants ingredients currently used in the South African animal industry was evaluated for H. midae. Soybean meal (96.86 %) and lupins (96.51 %) presented the highest apparent mean amino acid availability of all plant protein ingredients evaluated with H. midae. Canola meal (94.21 %), faba beans (92.87 %) sunflower meal (92.77 %), peanut meal (87.39 %) and cottonseed meal (85.15 %) presented higher apparent mean amino acid availability values than fish meal (82.75 %). Apparent protein digestibility was highly correlated (r = 0.99) with mean apparent amino acid availability, while true amino acid availability was 1.88 % units higher than apparent amino acid availability for all ingredients tested. Predicted apparent protein digestibility in compound diets was within 1.1-6.5 % of determined values. Calcium phosphate mono dibasic presented the lowest (P < 0.05) dietary phosphorus leaching (51.51 % maximum) and highest apparent phosphorus digestibility (66.27 %) in comparison to other inorganic phosphorus sources. Based on the method of direct experimentation to determine the optimal dietary protein level using graded levels of dietary protein 28.1-35.9 % dietary protein from good quality sources is recommended for maximum growth of juvenile H. midae. This study provides a scientifically sound research tool including a faecal collection technique, suitable marker and assay technique that could be use in further studies to improve least-cost diet formulation for H. midae. Future nutritional studies in H. midae should primarily concentrate on reducing dietary nutrient leaching and improving the intake of nutrients in order to properly evaluate responses of this species to different dietary regimes.
Keywords: Abalones -- Digestion; Abalones -- Nutrition